(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
The objective of this study was to a comparative study of stress and anxiety among ashramschool teachers and urban school teachers. It was a 2 x 2 factorial design was used. In this study 30teachers selected as sample from ashram school teachers (N=15) and urban school teachers (N=15) maleteachers mean age (32.17 ± 4.15) were selected as sample by using purposive sampling technique (n=30)from Nashik district. For the study stress and anxiety psychological variables selected and Anxiety andStress anxiety depression stress scale ADSS questionnaire implemented for collected obtained data. Aresult shown that data collected was analyzed by using two way analysis of variance applied andcompared the stress and anxiety level of ashram and urban school teachers and drawn the results.